Effect of blindfolding the lead resuscitator on frequency of closed-loop communication during veterinary cardio-pulmonary resuscitation training: a randomized, controlled pilot study - Walesby, Olivia X.; Stanzani, Giacomo; Kellett-Gregory, Lindsay; Seth, Mayank; Thomas, Emily K. (Frontiers in Veterinary Science, 2025)
ObjectiveTo evaluate the effect of blindfolding the lead resuscitator during veterinary cardiopulmonary resuscitation (CPR) simulation training sessions on frequency of completed closed-loop communication statements (CLC).DesignTen groups of staff volunteers were recruited for a prospective, randomized, blinded, observational pilot study over a 6-month period. Additionally, two associated online questionnaires were completed by participants.SettingPrivate veterinary referral hospital in the United Kingdom.InterventionForty volunteers were randomly allocated into ten groups of four. Each group was randomized as either control (CG) or blindfolded (BG) with the lead resuscitator always a veterinarian. The intervention involved the lead resuscitator wearing a blindfold during the third of four CPR simulation scenarios for the BG groups only.Measurements and main resultsVideo footage of Scenarios 2 (before) and 4 (after) the intervention was reviewed to quantify complete CLCs. Quantitative data were analyzed, and descriptive statistics calculated using GraphPadPrism (GraphPadPrism, Version9.3.1(350) forMacOSX, GraphPadSoftware, SanDiego, CA). Information from questionnaire responses was also analyzed. Statistical differences between the BGs and CGs were analyzed and there was no statistical difference in frequency of CLCs between the BGs and CGs during Scenario 2 (p = 0.76). In Scenario 4, however, following the intervention, there was a significant difference between BGs and CGs (p = 0.03), with a greater number of CLCs for the BGs compared with the CGs.ConclusionBlindfolding the lead resuscitator in veterinary CPR training scenarios may be an effective method to increase the incidence of complete CLCs. Further studies would be required to investigate whether this finding is replicated and retained in the longer term.